Individuals With the Rare Disease Pemphigus: A Quest for Diagnostic. (May 2019) - Le Hénaff, Yannick; Héas, Stéphane; Joly, Pascal
This qualitative study conducted in France of "individuals living with a pemphigus" (ILPs; N = 54) highlights the taxing diagnostic trajectory of those suffering from these rare autoimmune diseases. Beyond enduring a diagnostic period that may prove long, during their numerous medical appointments, these individuals internalize the expectations of the medical professionals who are treating them. In some cases, numerous inconclusive medical tests and, at times, a doctor's condescension may push the patient toward a process of renunciation. This article relates the ILPs' critiques of the medical work conducted during the trying diagnostic period.